What are the barriers faced by patients using insulin? A qualitative study of Malaysian health care professionals’ views - Khoo, E.M.; Lee, Y.K.; Ng, C.J.; Lee, P.Y.; Abdullah, K.L.; Low, W.Y.; Abdul Samad, A.; Chen, W.S. (Dove Medical Press, 2013)
Background: Patients with type 2 diabetes often require insulin as the disease progresses. However, health care professionals frequently encounter challenges when managing patients who require insulin therapy. Understanding how health care professionals perceive the barriers faced by patients on insulin will facilitate care and treatment strategies. Objective: This study explores the views of Malaysian health care professionals on the barriers faced by patients using insulin. Methods: Semi-structured qualitative interviews and focus group discussions were conducted with health care professionals involved in diabetes care using insulin. Forty-one health care professionals participated in the study, consisting of primary care doctors (n = 20), family medicine specialists (n = 10), government policymakers (n = 5), diabetes educators (n = 3), endocrinologists (n = 2), and one pharmacist. We used a topic guide to facilitate the interviews, which were audio-recorded, transcribed verbatim, and analyzed using a thematic approach. Results: Five themes were identified as barriers: side effects, patient education, negative perceptions, blood glucose monitoring, and patient adherence to treatment and follow-up. Patients perceive that insulin therapy causes numerous negative side effects. There is a lack of patient education on proper glucose monitoring and how to optimize insulin therapy. Cost of treatment and patient ignorance are highlighted when discussing patient self-monitoring of blood glucose. Finally, health care professionals identified a lack of a follow-up system, especially for patients who do not keep to regular appointments. Conclusion: This study identifies five substantial barriers to optimizing insulin therapy. Health care professionals who successfully identify and address these issues will empower patients to achieve effective self-management. System barriers require government agency in establishing insulin follow-up programs, multidisciplinary diabetes care teams, and subsidies for glucometers and test strips.